One-year epidemiological patterns of respiratory pathogens across age, gender, and seasons in Chengdu during the post-COVID era - Xiang Li; Jian Ma; Yi Li; Zhongliang Hu (Scientific Reports)
Abstract Respiratory tract infections caused by various pathogens remain a significant public health concern due to their high prevalence and potential for severe complications. This study systematically analyzed the epidemiological characteristics of six common respiratory pathogens—Chlamydia pneumoniae (CP), Mycoplasma pneumoniae (MP), Adenovirus (AdV), Influenza A virus (FluA), Influenza B virus (FluB), and Respiratory Syncytial Virus (RSV)—in patients from Sichuan Jinxin Xinan Women and Children’s Hospital between April 2023 and March 2024. Throat swab samples were collected from a total of 22,717 individuals. Each sample was processed using the AUTOMOLEC 3000 analyzer and the PCR-fluorescent probe method. The results showed that 10,171 (44.8%) individuals tested positive for at least one pathogen. MP had the highest overall positive rate (21.83%), followed by FluA (17.50%) and FluB (14.84%). MP showed the highest mean monthly (average) positive rate (16.84% ± 8.41). Significant differences were found between MP and AdV, CP and RSV in average positive rate (p < 0.05). Co-infection analysis revealed frequent associations between MP and AdV, MP and CP, and FluB with MP. Seasonal analysis indicated distinct peaks: FluA and FluB in winter, RSV in spring, and MP in summer, autumn and winter. Age-stratified analysis showed higher positivity rates of RSV in children aged 0–6 years, MP and CP in the 7–17 years group. Gender-based differences were only observed in RSV positive samples. These findings provide crucial insights into the prevalence and seasonal distribution of respiratory pathogens in Chengdu, offering valuable data to inform public health strategies in the post-COVID era.